PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASISSTED INDIVIDUALIZATION (TAI) DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 004 TELUK BINJAI - Suhaimi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This classroom action research aims to improve learning outcomes math class V students SD Negeri 004 Teluk Binjai Dumai Timur through cooperative learning team asissted individualization (TAI), conducted in September-November 2011. The subjects fifth grade students numbering SD Negeri 004 Teluk Binjai Dumai Timur students. Parameters measured research is student learning, student activities, complete learn student and teacher activities. The research instrument used consisted of two research instruments are instruments learning device consists of a syllabus, lesson plan (RPP), student worksheet (LKS) and data collection instruments consist of observation sheet student activity, observation sheet activities of teachers, test sheet. The results showed mastery learning in the first cycle was (60.00%) and the second cycle (93.30%). It can be concluded from the results of fifth grade students learn math SD Negeri 004 Teluk Binjai Dumai Timur can be improved through the cooperative model type asissted team individualization (TAI).